Influência da dentina bovina e do dispositivo de microtração na resistência de união de sistemas adesivos - Yamamoto, Lígia Tiaki [UNESP] (2014)
This project aimed to: simulate in finite element the stress distribution in Geraldeli and Modified's microtensile device during microtensile test; evaluate the bond strength between bovine dentin and composite resin bonded in two ways: enamel-pulp and pulp-enamel tubule directions, in two different devices for microtensile test: Geraldeli and Modified. The external geometry based on a real model was done in CAD software, experimental conditions were simulated (geometry, loading and fixation) and exported to structural analysis software Ansys. For microtensile test, bovine dentin blocks were bonded to composite resin with two different types of adhesives (conventional and self-etching), which were tested on both microtensile devices. The bond strength values were tabulated and subjected to ANOVA 3-WAY and Tukey's test statistical analysis (α = 0,05). Failures in each group were classified as adhesive, cohesive and mixed in stereomicroscope and SEM. The stress distribution in Geraldeli's device shows stress concentration in the adhesive region of the stick and distributed non-uniformly (oblique contours), with tension areas in the diagonal of the adhesive interface; Modified's device show stress concentration in the adhesive region too but more evenly distributed (parallel contours, radial to the adhesive area. Significant differences for the interaction between device device X dentine X adhesive (p = 0.001), device X dentine (p = 0.000), dentin X adhesive (p = 0.017) were observed. The adhesive and dentin were also influenced the results of microtensile test (p = 0.013 and 0.000, respectively). For Geraldeli device, conventional adhesive got better bond strength than the self-etching, in Pulp-Enamel; and Pulp-Enamel way got lower bond strength for the selfetching adhesives. For modified device, there was no statistical difference among the groups